Identification of Iron Ore Deposit in Sub-Surface using Resistivity and Induced Polarization Methods at Sarakaman, Sebuku Island, South Kalimantan - Merry Nur Rakhmawati; Sutrisno Sutrisno; Yanto Sudiyanto; Wahyu Hidayat (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2022)
Iron is the second most abundant metal on earth. Sebuku Island is one of the areas in Indonesia that has potential for laterite iron ore. This study aims to detect the presence of mineralized zones and estimate the volume of iron ore. Therefore, geophysical research was carried out using the resistivity method and the Induced Polarization methods with the Wenner-Schlumberger configuration. The research was carried out in 4 paths along 475 m with a space between the electrodes of 5 meters. Based on modeling, 20 iron ore deposits were found in the study area on all trajectories characterized by high chargeability values ranging from 251,55 – 810,55 ms which correlated with low resistivity values of 4,02 – 124,41 m. Then it was found that the direction of the distribution of iron ore deposits in the study area was north-south and there was no continuous zone of iron ore deposits due to the long distance of the path. The volume of iron ore deposits in the study area in an area of ±39 hectares is estimated to be around 1.807.614 m3 with total reserves of iron ore deposits of 7.230.456 tons.